The Effect of PbS Colloidal Quantum Dots with CdS and ZnS Coating on Photovoltaic Properties - Napasuda Wichaiyo; Mettaya Kitiwan; Qing Shen; Witoon Yindeesuk (My University, 2022)
In this research, we used the co-precipitation method to fabricate lead sulfide colloidal quantum dots (PbS CQDs) for photovoltaic cells. PbS CQDs were deposited uniformly on a titanium dioxide electrode by the dip-coating method. Photoelectrodes were prepared by coating layers using the successive ionic layer adsorption and reaction (SILAR) method. A solar simulation was used to investigate the photovoltaic properties of photoelectrodes under one sun illumination (100 mW/cm2) at room temperature (AM 1.5 G). The photovoltaic measurements demonstrated that TiO2/PbS CQDs with CdS and ZnS coating electrodes had a maximum power conversion efficiency (PCE) of 1.01 %. The crystallite size of PbS CQDs with different coating layers was analyzed using X-ray diffraction (XRD), and the crystallite size range was 6-7 nm. The existence of PbS CQDs and coating layers on the TiO2 electrodes was confirmed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). UV-visible spectroscopy was used to obtain the optical properties of the photoelectrodes. The optical band gap was 0.72-0.75 eV.
Keywords: Lead sulfide; Dip-coating; Quantum Dots Synthesis And Properties